2016
DOI: 10.3389/fnsys.2016.00028
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Propagation of Neuronal Sub-Population in Spontaneous Synchronized Bursts

Abstract: Repeating stable spatiotemporal patterns emerge in synchronized spontaneous activity in neuronal networks. The repertoire of such patterns can serve as memory, or a reservoir of information, in a neuronal network; moreover, the variety of patterns may represent the network memory capacity. However, a neuronal substrate for producing a repertoire of patterns in synchronization remains elusive. We herein hypothesize that state-dependent propagation of a neuronal sub-population is the key mechanism. By combining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…Dissociated culture of the cerebral cortex of rats was prepared on a high‐density CMOS microelectrode array (MEA). The culture protocol was based on a previous research with some modifications. Cerebral cortex was obtained from embryonic day 18 Wister rats and dissociated enzymatically in trypsin and physically by trituration.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dissociated culture of the cerebral cortex of rats was prepared on a high‐density CMOS microelectrode array (MEA). The culture protocol was based on a previous research with some modifications. Cerebral cortex was obtained from embryonic day 18 Wister rats and dissociated enzymatically in trypsin and physically by trituration.…”
Section: Methodsmentioning
confidence: 99%
“…In dissociated cultures of cerebral cortex of rodents, random Poisson‐like firings occur at early culture stages when neuronal network have not matured yet. As they mature, neuronal avalanche consists of diverse scale synchronized firings starts to appear . Synchronized firing patterns included within a neuronal avalanche changes from uniform to diverse as the culture matures .…”
Section: Background and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work is exploring the idea that spatiotemporal patterns of synchronized spontaneous activity in neuronal networks serve as memories [71], and it has recently been suggested that state-dependency accounts for the variety of such patterns [72**]. From an evolutionary perspective, SDL has also been conceptualized as a way to organize memories so that they can influence decision-making only under constrained conditions when access to specific information is particularly advantageous [5].…”
Section: Conclusion and Implications Of Sdlmentioning
confidence: 99%